Effect of Non-Uniform Vertical Excitations on Vertical Pounding Phenomenon in Continuous-Deck Curved Box Girder RC Bridges Subjected to Near-Source Earthquakes - Tamaddon, S.; Hosseini, M.; Vasseghi, A. (Taylor & Francis Ltd, 2022)
The geometry of skewed and curved bridges can cause complexity of their dynamic response and difficulty of analysis against earthquakes. In addition, when vibration occurs in the curved bridges, due to their specific geometry, the vertical, flexural, and torsional vibrations of the deck are coupled. The present study was carried out aiming to investigate the effect of non-uniform vertical excitation of the bridge piers with various vertical/horizontal acceleration ratio (V/H) on the pounding phenomenon in concrete curved bridges subjected to near-source earthquakes. For this purpose, the analytical method was employed using the expansion of the functions of structural dynamics on a two-span continuous concrete bridge model, consisting of continuous flexural/torsional beam elements for the deck, springs for the rubber bearings, and rods as the bridge piers. The non-uniform vertical excitations of the piers were induced to the whole system by the harmonic functions in the form of transient wave transfer functions, and then the equations of the entire system were solved using the Eigen functions. The induced waves can cause separation of the box girder deck from the rubber bearing along with the vertical and horizontal displacement as well as the torsion of the box girder around the longitudinal axis of the bridge. After each separation, the deck returns back and hit the rubber bearing, resulting in a vertical pounding force on the bearing and the pier. The analyses results show that when the curved beam is subjected to a non-uniform vertical excitation with a various V/H, the lateral displacement of the deck are up to 21% larger than when the bridge is excited by considering a value of V/H = 2/3. The results also show when the excitation frequencies are different in different piers of the bridge, the pounding force can be increased up to three times, for some specific curvature angle, comparing to the case of equal excitation frequency in all piers.
Keywords: Non-uniform seismic excitation; curved bridge; vertical earthquake excitation; vertical pounding; wave propagation; transient response